PENGEMBANGAN KOMIK DIGITAL BERBASIS CERITA FABEL UNTUK PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) UNTUK SISWA KELAS V SEKOLAH DASAR - Wana Maulini Parazian; Muhammad Fendrik; Dede Permana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In this study, the author encountered a problem frequently encountered, namely the limited use of digital learning media. Interviews, observations, and data obtained by the researcher in class V.C SDN 37 Pekanbaru showed that the use of digital learning media, especially in the Pancasila Student Profile Strengthening Project (P5) material, was still very limited. This was evidenced by interviews with the Principal, homeroom teacher, and students of class V.C SDN 37 Pekanbaru, namely the minimal use of interactive media caused students to appear passive and less enthusiastic in participating in project activities. This data is reinforced by the statement (Salahuddin et al., 2020) that the application of digital comics is expected to motivate a pleasant learning atmosphere. Children generally like illustrations, as are comics. In addition, the learning process will be more interesting, so that students' potential can be optimally developed in the 21st century (Zakiyah et al., 2022). However, the use of learning media at SDN 37 Pekanbaru is usually only obtained from printed books, so students easily get bored and their attention is often diverted during the learning process. This study used instruments in the form of interview sheets, questionnaires, and observation sheets. The R&D (Research and Development) method was employed. The development model used in this R&D is the 4D model. The stages of this development model consist of Define, Design, Development, and Disseminate. The results of this study indicate that the media is suitable for use after undergoing validity testing. The material validator yielded a percentage of 86.36%, categorized as very good/very suitable, the media validator yielded a percentage of 93.3%, categorized as very good/very suitable, and the language validator yielded percentages of 87.5% and 84.38%, categorized as very good/very suitable. Meanwhile, the results of the student response questionnaire yielded a percentage of 85.15%, categorized as very good. The student response questionnaire for the six P5 dimensions of the fable-based digital comic media yielded a percentage of 87.94%, categorized as very good.